1998
DOI: 10.1159/000024508
|View full text |Cite
|
Sign up to set email alerts
|

Serum Obtained from Rats after Partial Hepatectomy Enhances Growth of Cultured Colon Carcinoma Cells

Abstract: Tumour-bearing rats were randomized to a 70% partial hepatectomy or a sham operation. At days 1, 3 or 14, portal and systemic serum was obtained and colon carcinoma cells were cultured in the presence of 5, 10, 20 or 50% serum. Proliferation and epidermal growth factor receptor (EGFr) expression was measured in tumour cells. Proliferation was 25–40% higher in tumour cells cultured with portal serum after hepatectomy than after sham operation when using serum obtained at day 3, but not days 1 and 14 after opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In rats with colorectal liver tumours, it was found that timedependent changes in portal and systemic serum after PH were able to stimulate in vitro tumour cell growth (20). Therefore in the present study in humans, we measured changes in growth factor levels in portal and systemic serum after PH and after laparotomy alone.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In rats with colorectal liver tumours, it was found that timedependent changes in portal and systemic serum after PH were able to stimulate in vitro tumour cell growth (20). Therefore in the present study in humans, we measured changes in growth factor levels in portal and systemic serum after PH and after laparotomy alone.…”
Section: Discussionmentioning
confidence: 94%
“…Enhancement of tumour growth during liver regeneration has been described in animal experiments, and can possibly be explained by increased growth factor production in the liver and changes in serum growth factor levels (16)(17)(18)(19)(20)(21)(22). In rats with colorectal liver tumours, it was found that timedependent changes in portal and systemic serum after PH were able to stimulate in vitro tumour cell growth (20).…”
Section: Discussionmentioning
confidence: 97%
“…Hepatectomy in particular is known to stimulate growth of residual, both intra- and extrahepatic, tumor cells in animal experiments [134,135,136,137,138]. The stimulating effect is proportional to the extent of the resection [134, 138].…”
Section: Oncological Arguments With Indirect Evidence Pro and Contra mentioning
confidence: 99%
“…The stimulating effect is proportional to the extent of the resection [134, 138]. The stimulation is attributed to the production and release of growth factors for liver regeneration [134,135,136, 139], the intensity of which is also proportional to the extent of the liver resection [140]. For instance, hepatocyte growth factor, which strongly enhances liver regeneration after surgical resection or chemical damage, has also been found to increase colon cancer cell motility, growth and metastasis [135].…”
Section: Oncological Arguments With Indirect Evidence Pro and Contra mentioning
confidence: 99%
“…The angiogenic response caused by increased expression of FGF and other growth factors may favor the proliferation of residual tumor cells [162][163][164] and also have cytoprotective effects [165]. The role of epidermal growth factor and hepatocyte growth factor also has long been recognized to be a major factor in liver regeneration and potential tumor growth [166,167]. The influence of focal hyperthermia on the expression of these regenerative growth factors is however limited [164].…”
Section: Cytokine Release and Adhesion Moleculesmentioning
confidence: 99%